Transformation of english listening learning in second grade elementary school through the Total Physical Response (TPR) method - Berliana Fika Meysa Ayu Widuri; Abdurrohman Muzakki; Heru Wardana Yoga; Nagoor Meera Abdullah; Deny Pradana Saputro (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
Listening comprehension is a fundamental skill in early foreign language learning; however, it is often underdeveloped in elementary classrooms due to low student engagement and conventional instructional practices. This study aims to examine the effectiveness of the Total Physical Response (TPR) method in improving English listening comprehension among second-grade elementary school students. A quasi-experimental nonequivalent control group pretest–posttest design was employed involving 60 students from an elementary school in East Jakarta, Indonesia. The participants were divided into an experimental group (n = 30) that received TPR-based instruction and a control group (n = 30) that received conventional instruction over four weeks. Quantitative data were collected via listening comprehension tests and analyzed using independent-samples t-tests. The results indicated that the experimental group achieved significantly higher posttest scores (M = 80.17) than the control group (M = 68.50), t(58) = 3.25, p = .003, with a large effect size (Cohen's d = 0.84). These findings suggest that TPR is an effective and developmentally appropriate approach for enhancing English listening comprehension in early elementary education.